Concurrent validity and intratester reliability of the video‐based system for measuring gait poststroke. (16th August 2019) - Aung, Nilar; Bovonsunthonchai, Sunee; Hiengkaew, Vimonwan; Tretriluxana, Jarugool; Rojasavastera, Rommanee; Pheung‐Phrarattanatrai, Anuchai
Abstract: Background and purpose: Spatio‐temporal parameters are commonly used in gait assessment. Advanced tools provide valid and reliable data, considered very effective for physiotherapy intervention. However, these tools may be limited in clinical usage caused by complicated applicability, inaccessibility, and high cost. Therefore, a video‐based system is an alternative choice that is easy and affordable for the clinical setting. The purpose of the study was to evaluate the concurrent validity of the video‐based system against the validated instrumented gait system (Force Distribution Measurement [FDM]) on the spatio‐temporal gait parameters in individuals with stroke. In addition, the intratester reliability of a novice tester was determined. Methods: Twenty individuals with stroke participated in the study. Gait was captured by the video‐based and FDM systems simultaneously to measure the degree of concurrent validity. Parameters composed of the affected and unaffected step lengths (cm) and step time (s), stride length (cm), gait velocity (m/s), and cadence (steps/min). Pearson correlation coefficient, paired t test, and intraclass correlation coefficient (ICC) were used to determine the concurrent validity, the difference of the data, and intratester reliability. Results: All spatio‐temporal gait parameters showed excellent degrees of correlation ( r p = .94 to.99, p <.001) between the video‐based and FDM systems. No significant difference in all parameters was found between the two systems. Excellent intratester reliability (ICC3, 1 = 0.91 to 0.99, p < .001) of all gait parameters were found in a novice tester. Conclusion: The video‐based system was valid and reliable for a novice tester to measure the spatio‐temporal gait parameters in individuals with stroke.